Determinan Inovasi Perusahaan Menengah Besar di Sumatera Utara - Rapita Handayani; Rossanto Dwi Handoyo (Inovasi, 2020)
This study aims to find out the innovation characteristics of large medium enterprises in North Sumatera. In addition, this study aims to set the determinants of innovation using the Negative Binomial Regression method. This study processed 12,342 microdata of large-medium enterprises obtained from the 2016-Census of Economy- Advanced on Data Collection for Large-Medium Enterprises (UMB) and Micro-Small Enterprises (UMK). This data collection was carried out by Statistics Indonesia in 2017. Descriptive analysis results show that marketing innovation and product innovation are the most common types of innovation conducted by UMB in North Sumatera. Internet use and business development variables are the most widely used indicators of innovation, while research and development (R&D) activities and ownership of intellectual property variables are the least indicators of innovation. From the results of inference analysis, it was found that the economic sector category model that all of significant independent variables (innovation indicators) are the category models of C (Manufacturing), G (Wholesale &Retail Trade, Repair of Motor Vehicles & Motorcycles), H (Transportation & Storage), I (Accommodation & Food Service), K (Financial & Insurance), N (Leasing and Leasing without Option Rights, Employment, Travel Agencies, and Other Business Supports), P (Education), R and S (Arts, entertainment recreation, and Other service activities). Workforce training and business development variables are one of the important innovation indicators because it affects almost all economic sectors.